Effects of ultrasound pretreatment on functional property, antioxidant activity, and digestibility of soy protein isolate nanofibrils - Hu, Anna; Li, Liang (Ultrasonics sonochemistry, 2022)
•Low amplitude ultrasound improved the solubility, EAI and WAC of SPI nanofibrils.•High amplitude ultrasound improved the foaming capacity and foaming stability.•Antioxidant activity of SPI nanofibrils was improved by 20% amplitude ultrasound.•In vitro digestion rate of 80% amplitude ultrasound-SPI nanofibrils were the highest. Nanofibrils, an effective method to modulate the functional properties of proteins, can be promoted by ultrasound pretreatment. This study investigated the effect of ultrasound pretreatment on the structure, functional property, antioxidant activity and digestibility of soy protein isolate (SPI) nanofibrils. The results showed that high amplitude ultrasound had a significant effect on structure of SPI nanofibrils. SPI nanofibrils pretreated by 80% amplitude ultrasound showed a blueshift of the amide II band in Fourier transform infrared spectroscopy (FTIR), resulted in more tryptophan residues being buried and increased the crystallinity. Low amplitude ultrasound (20%) pretreatment significantly improved the solubility, emulsifying activity index (EAI) and water absorption capacity (WAC) of SPI nanofibrils, but 80% amplitude ultrasound pretreatment of SPI nanofibrils reduced emulsifying stability index (ESI). High amplitude ultrasound (60% and 80%) pretreatment of SPI nanofibrils improved the foaming capacity and foaming stability and decreased denaturation temperature. DPPH radical scavenging activity of SPI nanofibrils were significantly improved by ultrasound pretreatment. 20% amplitude ultrasound pretreatment improved DPPH, ABTS radical scavenging activity and ferric reducing antioxidant power of SPI nanofibrils. The digestion rate of 80% amplitude ultrasound-pretreated nanofibrils were consistently higher, and SPI nanofibrils pretreated by ultrasound were more fragmented and shorter after simulating gastrointestinal digestion. This study would expand the application of food-grade protein nanofibrils in the food industry.